A high-efficiency adsorbent for uremia and preparation method thereof

Through the preparation method of adsorbents that combine modified chitosan and modified carboxymethylcellulose with molybdenum disulfide composite nanomaterials, the problem of poor adsorption of existing adsorbents on uremia toxins is solved, and efficient and rapid toxin adsorption and good biocompatibility are achieved.

CN119075931BActive Publication Date: 2025-02-28JIANGSU JEREH MEDICAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411439765.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-28
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing adsorbents are not effective in adsorbing uremia toxins, especially inadequate adsorption performance for urea and creatinine-based small molecule toxins with large metabolic production.

Method used

The high-efficiency adsorbent preparation method is adopted to combine modified chitosan and modified carboxymethylcellulose with molybdenum disulfide composite nanomaterials, and the modification is introduced through carboxymethylation modification and acylation reagents to improve adsorption performance and biocompatibility.

Benefits of technology

It has achieved rapid adsorption and high-volume adsorption of uremia toxins, with good biocompatibility and hemocompatibility, and is suitable for wearable artificial kidneys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086042260000081
    Figure BDA0005086042260000081
  • Figure BDA0005086042260000091
    Figure BDA0005086042260000091
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbent preparation, and provides a kind of efficient adsorbent and preparation method thereof for uremia, the preparation method of the efficient adsorbent comprises the following steps: (1) modified chitosan is dispersed in deionized water, 1,2-dichloroethane is added, ultrasonic 20-40min, adsorbent material is added, stirring 10-15h, and reactant is obtained; (2) modified carboxymethyl cellulose, sodium hydroxide, deionized water are mixed, stirring 1-3h, reactant and epichlorohydrin obtained in step (1) are added, heated to 50-70℃, heat preservation reaction 2-4h, washing, drying, and efficient adsorbent is obtained. The efficient adsorbent of the present invention has fast adsorption rate and high adsorption capacity for uremic toxins, and has good biocompatibility and blood compatibility, and has good market prospects in the field of wearable artificial kidney.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent preparation, and in particular relates to a high-efficiency adsorbent for uremia and a preparation method thereof. Background Art

[0002] In recent years, uremia has seriously threatened human health, causing varying degrees of disorder in the normal physiological functions of the human body and endangering life. At present, common treatments for uremia include kidney transplantation, hemodialysis, hemoperfusion and peritoneal dialysis. With the continuous development of dialysis technology, wearable artificial kidneys have brought convenience to the treatment of a large number of uremia patients. The core of this is that the dialysate can be repeatedly recycled by regularly replacing the adsorbent. Ordinary adsorbent materials such as activated carbon, zirconium phosphate and zirconium oxide can adsorb ions and toxins, but they have poor adsorption effects on small molecule toxins such as urea and creatinine that are produced in large amounts by metabolism.

[0003] Molybdenum disulfide is a nanomaterial with a special layered structure. Due to its unique physical and chemical properties, it has shown wide application potential in many fields. In the field of artificial kidney technology, the adsorption performance of molybdenum disulfide has attracted particular attention, mainly due to its large specific surface area and abundant active sites on the edge. However, the application of molybdenum disulfide in artificial kidney technology still faces challenges, including how to improve its stability in the body, how to ensure its long-term biocompatibility and blood compatibility, etc.

[0004] Chinese patent CN113680328 B discloses a cross-linked cellulose@molybdenum disulfide aerogel composite adsorbent and its preparation method and application. With cross-linked cellulose aerogel as a carrier, molybdenum disulfide nanoparticles are directly doped into a cellulose suspension by a premixing-crosslinking fixation-freezing pore-forming method, and then a cross-linking agent is added to form a three-dimensional network structure of cellulose to fix the molybdenum disulfide particles. The present invention combines the good hydraulic properties of the carrier with the excellent adsorption selectivity of molybdenum disulfide for lead ions, and the composite adsorbent has excellent adsorption capacity and fast adsorption kinetics for lead ions; however, the adsorption effect of the composite adsorbent of cellulose and molybdenum disulfide on uremic toxins is unknown and remains to be studied.

[0005] Therefore, there is an urgent need to develop an efficient adsorbent for uremia that has excellent adsorption performance for uremic toxins. Summary of the invention

[0006] In view of the existing technical problems, the purpose of the present invention is to provide a high-efficiency adsorbent for uremia and a preparation method thereof. The high-efficiency adsorbent of the present invention has a fast adsorption rate and high adsorption capacity for uremic toxins, and has good biocompatibility and blood compatibility, and has a good market prospect in the field of wearable artificial kidneys.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] In one aspect, the present invention provides a method for preparing a high-efficiency adsorbent for uremia, comprising the following steps:

[0009] (1) dispersing the modified chitosan in deionized water, adding 1,2-dichloroethane, ultrasonicating for 20-40 min, adding the adsorbent material, stirring for 10-15 h, and obtaining a reactant;

[0010] (2) Modified carboxymethyl cellulose, sodium hydroxide and deionized water are mixed and stirred for 1-3 hours, the reactant obtained in step (1) and epichlorohydrin are added, the mixture is heated to 50-70° C., the mixture is kept warm for 2-4 hours, and the mixture is washed and dried to obtain a high-efficiency adsorbent.

[0011] The reaction mechanism and effects of the present invention are as follows:

[0012] 1. Chitosan is a natural alkaline polysaccharide with good biocompatibility, low cytotoxicity, and good moisture absorption and moisture retention. Chitosan has a good affinity for urea and creatinine because urea and creatinine can destroy the hydrogen bond structure in the chitosan structure and then adsorb on the surface of chitosan.

[0013] The present invention first performs carboxymethylation modification on chitosan. The carboxymethylated chitosan can be stably combined with the surface of the adsorption material to play a synergistic adsorption role. Further, an acylating agent is introduced to enhance the adsorption performance of urea and creatinine substances. The modified chitosan not only increases the water solubility, but also improves the affinity with urea and creatinine substances, and the adsorption capacity of similar toxins becomes stronger. In addition, the modified chitosan has extremely high biocompatibility, which can further reduce the cytotoxicity of molybdenum disulfide, and obtain an adsorbent with high adsorption and high selectivity.

[0014] 2. The surface of carboxymethyl cellulose contains abundant carboxyl and hydroxyl groups, but its application as an adsorbent is limited due to its limited adsorption capacity. Studies have found that carboxymethyl cellulose has the ability to coordinate with multivalent metal ions to form a three-dimensional network structure, and this property enhances its application potential in the field of adsorption. At the same time, urea molecules can also interact with the unoccupied d orbitals of metal ions to form complexes.

[0015] The present invention modifies carboxymethyl cellulose to synthesize modified carboxymethyl cellulose rich in aldehyde groups and copper ions. On the one hand, the modified carboxymethyl cellulose can form an irreversible covalent bond between an electrophilic carbonyl group and a weakly nucleophilic urea molecule, and improve the adsorption performance by the combined action of the copper ion and the aldehyde double chemical adsorption site. On the other hand, the modified carboxymethyl cellulose can reduce the adsorption of plasma proteins and platelets by increasing the negative charge on the surface of the material, thereby playing an anticoagulant role and making it have good blood compatibility.

[0016] In some embodiments, the method for preparing the modified chitosan comprises the following steps:

[0017] A1. Ultrasonic dispersion of sodium carbonate in deionized water to obtain a sodium carbonate solution for later use;

[0018] A2. Sodium hydroxide, chitosan and deionized water were mixed and stirred for 2.5-3.5h, chloroacetic acid was added in 4-6 portions, stirred and heated to 80-100°C, refluxed for 4-6h, 0.5-1h after the reaction started, sodium carbonate solution obtained in step A1 was added every 20-35min to control the pH value to be neutral, filtered, precipitated with anhydrous ethanol, centrifuged, washed, acidified, and dried to obtain carboxymethyl chitosan;

[0019] A3. Disperse the carboxymethyl chitosan obtained in step A2 with deionized water, add an acylating agent, heat to 90-120°C for reaction for 0.5-1.5h, cool, precipitate with anhydrous ethanol, centrifuge, wash, and dry to obtain modified chitosan.

[0020] In some embodiments, the mass ratio of chitosan to chloroacetic acid in step A2 is 1:(3.5-5).

[0021] In some embodiments, the mass ratio of carboxymethyl chitosan to acylating agent in step A3 is 1:(7-10).

[0022] In some embodiments, the method for preparing the adsorbent material comprises the following steps:

[0023] S1. Mix ammonium molybdate tetrahydrate and thiourea and perform a hydrothermal reaction to prepare nano-molybdenum disulfide;

[0024] S2. The nano-molybdenum disulfide obtained in step S1, cerium nitrate hexahydrate, and deionized water are mixed, ultrasonically dispersed for 5-10 minutes, hydrochloric acid is added, heated to 90-100°C, stirred for 10-25 minutes, cooled, washed, and dried to obtain a CeO2 / MoS2 composite nanomaterial;

[0025] S3. The CeO2 / MoS2 composite nanomaterial obtained in step S2 and the modified liquid of 1-2 mg / mL were heated and ultrasonically treated, and then deionized water was added, centrifuged once, the precipitate was washed, and then dispersed with deionized water, centrifuged twice, the upper liquid was taken, and dried to obtain a modified CeO2 / MoS2 composite nanomaterial;

[0026] S4. Disperse the modified CeO2 / MoS2 composite nanomaterial in deionized water, add a surfactant, ultrasonically disperse, add the modified graphene, ultrasonically disperse, then add a reducing agent, perform a hydrothermal reaction, wash, and dry to obtain an adsorption material.

[0027] In some embodiments, the specific steps of step S1 are as follows:

[0028] Add ammonium molybdate tetrahydrate, thiourea and deionized water into a reactor, perform ultrasonic treatment at 100-200W for 20-45min, heat to 180-210°C, react for 16-24h, cool, centrifuge once, take the precipitate, wash it with deionized water 3-4 times, disperse it with deionized water, centrifuge it twice, take the upper liquid, and dry it to obtain nano molybdenum disulfide.

[0029] In some embodiments, the method for preparing the modified carboxymethyl cellulose comprises the following steps:

[0030] B1. Mix carboxymethyl cellulose and deionized water, stir, add 1-2 mol / L sulfuric acid aqueous solution, adjust the pH to 3-4, add sodium periodate, heat to 35-40 ° C for 3-4h, then add ethylene glycol and continue stirring for 30-45min to obtain a reaction product;

[0031] B2. The reaction product obtained in step B1 and 0.07-0.15 mol / L copper nitrate aqueous solution are mixed, heated to 35-45° C. for reaction for 4-5 h, washed, and dried to obtain modified carboxymethyl cellulose.

[0032] In some embodiments, the mass ratio of carboxymethyl cellulose to sodium periodate in step B1 is 1:(0.9-1.1).

[0033] In some embodiments, the mass ratio of the modified chitosan, 1,2-dichloroethane and the adsorbent material in step (1) is 1:(12-18):(4-7).

[0034] In some embodiments, the mass ratio of the modified carboxymethyl cellulose to epichlorohydrin in step (2) is 1:(3.5-6).

[0035] In some embodiments, the mass ratio of modified chitosan to modified carboxymethyl cellulose is 1:(1.8-2.2).

[0036] Another aspect of the present invention provides a high-efficiency adsorbent obtained by the above preparation method.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The high-efficiency adsorbent of the present invention has a fast adsorption rate for uremic toxins, a high adsorption capacity, and good biocompatibility and blood compatibility, and has a good market prospect in the field of wearable artificial kidneys.

[0039] 2. The present invention performs carboxymethyl modification on chitosan and introduces an acylating agent to improve the stability of the adsorbent, which not only increases the water solubility, but also improves the affinity with urea and creatinine, and enhances the adsorption capacity of similar toxins. In addition, the modified chitosan has extremely high biocompatibility and can further reduce the cytotoxicity of molybdenum disulfide.

[0040] 3. The present invention modifies carboxymethyl cellulose to synthesize modified carboxymethyl cellulose rich in aldehyde groups and copper ions, which can not only improve the adsorption performance, but also reduce the adsorption of plasma proteins and platelets by increasing the negative charge on the surface of the material, thereby playing an anticoagulant role and making it have good blood compatibility. DETAILED DESCRIPTION

[0041] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0042] According to the ratios of the raw materials and the preparation methods specified in the following examples and comparative examples, various high-efficiency adsorbents were prepared.

[0043] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:

[0044] Chitosan: purchased from Guangdong Hongyou Biotechnology Co., Ltd.;

[0045] Carboxymethyl cellulose: purchased from Anhui Tongchuang Fanxing Biotechnology Co., Ltd.;

[0046] Other raw materials are not specially specified and can be purchased from the market.

[0047] Preparation Example 1

[0048] The preparation method of modified chitosan A comprises the following steps:

[0049] A1. Ultrasonic dispersion of 1 g of sodium carbonate in 90 ml of deionized water to obtain a sodium carbonate solution for later use;

[0050] A2. 5 g of sodium hydroxide, 2 g of chitosan and 40 g of deionized water were mixed and stirred for 3 h. 8 g of chloroacetic acid (1.6 g each time) was added in 5 portions, stirred and heated to 90 ° C., refluxed for 5 h. After 1 h of the reaction, the sodium carbonate solution obtained in step A1 was added every 30 min to control the pH value to be neutral. The clear liquid was filtered and precipitated with anhydrous ethanol, centrifuged, washed with anhydrous ethanol 4 times, acidified with acetic acid, and freeze-dried at -40 ° C for 24 h to obtain carboxymethyl chitosan;

[0051] A3. Disperse 1.5 g of carboxymethyl chitosan obtained in step A2 with 100 ml of deionized water, add 12.75 g of terephthaloyl chloride, heat to 105 ° C for 1 h, cool to room temperature, precipitate with anhydrous ethanol, centrifuge, wash 4 times with anhydrous ethanol, and freeze-dry at -40 ° C for 24 h to obtain modified chitosan A.

[0052] Preparation Example 2

[0053] The preparation method of modified chitosan B is the same as that of Preparation Example 1, except that the amount of chloroacetic acid added in step A2 is 6.6 g (1.32 g each time).

[0054] Preparation Example 3

[0055] The preparation method of modified chitosan C is the same as that of Preparation Example 1, except that the amount of terephthaloyl chloride added in step A3 is 10 g.

[0056] Preparation Example 4

[0057] The preparation method of modified carboxymethyl cellulose A comprises the following steps:

[0058] B1. 3 g of carboxymethyl cellulose was mixed with 120 ml of deionized water, stirred for 3 h, 1.5 mol / L of sulfuric acid aqueous solution was added dropwise to adjust the pH value to 3.5, 3 g of sodium periodate was added, heated to 35 ° C for 4 h, and then 8 ml of ethylene glycol was added and stirred for 30 min to terminate the reaction to obtain a reaction product;

[0059] B2. Mix 2 g of the reaction product obtained in step B1 with 100 ml of 0.1 mol / L copper nitrate aqueous solution, heat to 40°C for reaction for 5 h, wash with deionized water until neutral, and freeze-dry at -40°C for 24 h to obtain modified carboxymethyl cellulose A.

[0060] Preparation Example 5

[0061] The preparation method of modified carboxymethyl cellulose B is the same as that of Preparation Example 4, except that the amount of sodium periodate added is 2.25 g.

[0062] Preparation Example 6

[0063] The preparation method of the adsorption material comprises the following steps:

[0064] S1. 1.5 g of ammonium molybdate tetrahydrate, 3.15 g of thiourea and 50 ml of deionized water were added to the reactor, ultrasonicated at 150 W for 35 min, heated to 200 ° C, reacted for 20 h, cooled to room temperature, centrifuged at 12000 rpm for 30 min, the precipitate was washed with deionized water 4 times, dispersed with deionized water, centrifuged at 4500 rpm for 15 min, the upper layer was taken, and dried at 60 ° C for 48 h to obtain nano molybdenum disulfide;

[0065] S2. 1 g of nano-molybdenum disulfide obtained in step S1, 0.37 g of cerium nitrate hexahydrate, and 200 ml of deionized water were mixed, ultrasonically dispersed for 8 min, 5 ml of 0.12 mol / L hydrochloric acid was added, heated to 95 ° C, stirred for 15 min, cooled to room temperature, washed 3 times with anhydrous ethanol, then washed 3 times with deionized water, and dried at 60 ° C for 16 h to obtain CeO2 / MoS2 composite nanomaterials;

[0066] S3. 1 g CeO2 / MoS2 composite nanomaterial obtained in step S2 and 700 ml 1.5 mg / mL 6-amino-1-mercaptohexane hydrochloride aqueous solution were heated to 35 ° C, ultrasonicated at 150 W for 20 min, and then 500 ml of deionized water was added, centrifuged at 12000 rpm for 30 min, the precipitate was washed 4 times with deionized water, dispersed with 300 ml of deionized water, centrifuged at 4500 rpm for 15 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain a modified CeO2 / MoS2 composite nanomaterial;

[0067] S4. Disperse 0.5 g of modified CeO2 / MoS2 composite nanomaterial in 100 ml of deionized water, add 50 mg of dodecyltrimethylammonium bromide, ultrasonically disperse at 200 W for 20 min, add 10 mg of modified graphene, ultrasonically disperse at 500 W for 40 min, then add 0.2 g of thiourea, heat to 180 ° C, stir to react for 6 h, cool to room temperature, wash with deionized water 4 times, dry to constant weight at a vacuum degree of 1.0 Pa and a temperature of -40 ° C to obtain an adsorbent material;

[0068] Wherein, the preparation method of the modified graphene comprises the following steps:

[0069] 1 g of graphene oxide and 100 ml of deionized water were mixed, and ultrasonic dispersion was performed at 100 W for 30 min. Then, 2.4 g of chloroacetic acid and 3.6 g of sodium hydroxide were added, and ultrasonic dispersion was performed at 200 W for 45 min. The mixture was stirred for 16 h, centrifuged, washed with deionized water until neutral, freeze-dried at -30 ° C for 12 h, and ground to obtain modified graphene.

[0070] Example 1

[0071] A method for preparing a high-efficiency adsorbent for uremia comprises the following steps:

[0072] (1) Dispersing 1 g of modified chitosan A in 100 ml of deionized water, adding 15 g of 1,2-dichloroethane, ultrasonicating for 30 min, adding 5.5 g of adsorbent material, stirring for 12 h, and obtaining a reactant;

[0073] (2) 2 g of modified carboxymethyl cellulose A, 4 g of sodium hydroxide, and 50 ml of deionized water were mixed and stirred for 2 h. The reactant obtained in step (1) and 9.5 g of epichlorohydrin were added, heated to 60° C., kept warm for 3 h, washed with deionized water 4 times, and freeze-dried at -40° C. for 48 h to obtain a high-efficiency adsorbent.

[0074] Example 2

[0075] A method for preparing a high-efficiency adsorbent for uremia comprises the following steps:

[0076] (1) Dispersing 1 g of modified chitosan A in 100 ml of deionized water, adding 12 g of 1,2-dichloroethane, ultrasonicating for 20 min, adding 4 g of adsorbent material, stirring for 10 h, and obtaining a reactant;

[0077] (2) 2 g of modified carboxymethyl cellulose A, 4 g of sodium hydroxide, and 50 ml of deionized water were mixed and stirred for 1 h. The reactant obtained in step (1) and 7 g of epichlorohydrin were added, heated to 70° C., kept warm for 2 h, washed 4 times with deionized water, and freeze-dried at -40° C. for 48 h to obtain a high-efficiency adsorbent.

[0078] Example 3

[0079] A method for preparing a high-efficiency adsorbent for uremia comprises the following steps:

[0080] (1) Dispersing 1 g of modified chitosan A in 100 ml of deionized water, adding 18 g of 1,2-dichloroethane, ultrasonicating for 40 min, adding 7 g of adsorbent material, stirring for 15 h, and obtaining a reactant;

[0081] (2) 2 g of modified carboxymethyl cellulose A, 4 g of sodium hydroxide, and 50 ml of deionized water were mixed and stirred for 3 h. The reactant obtained in step (1) and 12 g of epichlorohydrin were added, heated to 50° C., kept warm for 4 h, washed with deionized water 4 times, and freeze-dried at -40° C. for 48 h to obtain a high-efficiency adsorbent.

[0082] Example 4

[0083] The preparation method of a high-efficiency adsorbent for uremia is the same as that of Example 1, except that an equal amount of modified chitosan B is used to replace modified chitosan A.

[0084] Example 5

[0085] The preparation method of a high-efficiency adsorbent for uremia is the same as that of Example 1, except that an equal amount of modified chitosan C is used to replace modified chitosan A.

[0086] Example 6

[0087] The preparation method of a high-efficiency adsorbent for uremia is the same as that in Example 1, except that an equal amount of modified carboxymethyl cellulose B is used to replace modified carboxymethyl cellulose A.

[0088] Example 7

[0089] The preparation method of a high-efficiency adsorbent for uremia is the same as that in Example 1, except that the added amount of modified chitosan A is 0.68 g.

[0090] Example 8

[0091] The preparation method of a high-efficiency adsorbent for uremia is the same as that in Example 1, except that the amount of epichlorohydrin added is 12.4 g.

[0092] Comparative Example 1

[0093] The preparation method of a high-efficiency adsorbent for uremia is the same as that in Example 1, except that an equal amount of commercially available chitosan is used to replace modified chitosan A.

[0094] Comparative Example 2

[0095] The preparation method of a high-efficiency adsorbent for uremia is the same as that in Example 1, except that an equal amount of commercially available carboxymethyl cellulose is used instead of modified carboxymethyl cellulose A.

[0096] Effect evaluation:

[0097] The high-efficiency adsorbents prepared in the above Examples 1-8 and Comparative Examples 1-2 were tested and analyzed, and the specific results are shown in Table 1.

[0098] Performance Test:

[0099] (1) Adsorption performance: Take 10 ml of plasma solution containing urea and creatinine, add 5 g of the above adsorbent, seal, and shake in a shaker at 37°C for 2 h. After the adsorption is completed, measure the changes of each toxin, and calculate the adsorption rate of each toxin by the adsorbent based on the concentration difference before and after adsorption. Repeat three times and take the average value;

[0100] (2) Blood compatibility: Soak the adsorbent in physiological saline for 30 min, filter the surface water with a sand core funnel, weigh 1 g of adsorbent and add 5 ml of fresh human blood, place in a 37°C water bath to maintain constant temperature, take out after 2 hours, and measure the changes in blood cells on a blood cell analyzer. Repeat three times and take the average value.

[0101] Table 1

[0102]

[0103]

[0104] From the results in Table 1, it can be seen that the adsorbents prepared in Examples 1-3 have good adsorption performance and good blood compatibility.

[0105] Examples 4-5 and Comparative Example 1 Compared with Example 1, when preparing modified chitosan, Example 4 changed the mass ratio of chitosan and chloroacetic acid, and the amount of grafted carboxyl groups was reduced; Example 5 changed the mass ratio of carboxymethyl chitosan and acylating agent, and the carbonyl content during the reaction was reduced. Comparative Example 1 used an equal amount of commercially available chitosan to replace modified chitosan A, which could not combine with the adsorption material, and both reduced the adsorption performance and blood compatibility of the adsorbent.

[0106] Example 6 and Comparative Example 2 Compared with Example 1, when preparing carboxymethyl cellulose, Example 6 changes the mass ratio of carboxymethyl cellulose and sodium periodate, and the aldehyde groups obtained by the ring-opening reaction are reduced. Comparative Example 2 uses an equal amount of commercially available carboxymethyl cellulose to replace modified carboxymethyl cellulose A, and the dual chemical adsorption sites of copper ions and aldehyde groups are lost, both of which affect the adsorption performance and blood compatibility of the adsorbent.

[0107] Compared with Example 1, Example 7 changes the mass ratio of modified chitosan, 1,2-dichloroethane and adsorbent material, and the compatibility of the obtained reactants is weakened, thereby affecting the adsorption performance and blood compatibility of the adsorbent.

[0108] Compared with Example 1, Example 8 changes the mass ratio of modified carboxymethyl cellulose and epichlorohydrin to, excessive cross-linking will increase the internal pores and make the pore size too small, resulting in a decrease in the adsorption effect of the adsorbent.

[0109] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.

Claims

1. A method for preparing a highly efficient adsorbent for uremia, characterized in that: The following steps are included: (1) Dispersing the modified chitosan in deionized water, adding 1,2-dichloroethane, ultrasonicating for 20-40 min, adding the adsorbent material, stirring for 10-15 h, and obtaining a reactant; (2) Mix modified carboxymethyl cellulose, sodium hydroxide and deionized water, stir for 1-3 hours, add the reactant obtained in step (1) and epichlorohydrin, heat to 50-70° C., keep warm for 2-4 hours, wash and dry to obtain a high-efficiency adsorbent; The preparation method of the modified chitosan comprises the following steps: A1. Ultrasonic dispersion of sodium carbonate in deionized water to obtain a sodium carbonate solution for later use; A2. Sodium hydroxide, chitosan and deionized water are mixed and stirred for 2.5-3.5h, chloroacetic acid is added in 4-6 portions, stirred and heated to 80-100°C, refluxed for 4-6h, 0.5-1h after the reaction starts, sodium carbonate solution obtained in step A1 is added every 20-35min to control the pH value to be neutral, filtered, precipitated with anhydrous ethanol, centrifuged, washed, acidified, and dried to obtain carboxymethyl chitosan; A3. The carboxymethyl chitosan obtained in step A2 is dispersed in deionized water, an acylating agent is added, and the reaction is heated to 90-120°C for 0.5-1.5h, cooled, precipitated with anhydrous ethanol, centrifuged, washed, and dried to obtain modified chitosan; The preparation method of the adsorbent material comprises the following steps: S1. Mix ammonium molybdate tetrahydrate and thiourea and perform a hydrothermal reaction to prepare nano-molybdenum disulfide; S2. The nano-molybdenum disulfide obtained in step S1, cerium nitrate hexahydrate, and deionized water are mixed, ultrasonically dispersed for 5-10 minutes, hydrochloric acid is added, heated to 90-100°C, stirred for 10-25 minutes, cooled, washed, and dried to obtain a CeO2 / MoS2 composite nanomaterial; S3. The CeO2 / MoS2 composite nanomaterial obtained in step S2 and the modified liquid of 1-2 mg / mL were heated and ultrasonically treated, and then deionized water was added, centrifuged once, the precipitate was washed, and then dispersed with deionized water, centrifuged twice, the upper liquid was taken, and dried to obtain a modified CeO2 / MoS2 composite nanomaterial; S4. Disperse the modified CeO2 / MoS2 composite nanomaterial in deionized water, add a surfactant, ultrasonically disperse, add modified graphene, ultrasonically disperse, then add a reducing agent, hydrothermally react, wash, and dry to obtain an adsorbent material; wherein the modified liquid is an aqueous solution of 6-amino-1-mercaptohexane hydrochloride; the preparation method of modified graphene comprises the following steps: mixing graphene oxide and deionized water, ultrasonically disperse, then adding chloroacetic acid and sodium hydroxide, ultrasonically, stirring for 10-16h, centrifugally washing, drying, and grinding to obtain modified graphene; The preparation method of the modified carboxymethyl cellulose comprises the following steps: B1. Mix carboxymethyl cellulose and deionized water, stir, add 1-2 mol / L sulfuric acid aqueous solution, adjust the pH value to 3-4, add sodium periodate, heat to 35-40°C for 3-4h, then add ethylene glycol and continue stirring for 30-45min to obtain a reaction product; B2. The reaction product obtained in step B1 and 0.07-0.15 mol / L copper nitrate aqueous solution are mixed, heated to 35-45° C. for reaction for 4-5 h, washed, and dried to obtain modified carboxymethyl cellulose.

2. The method for preparing a highly efficient adsorbent for uremia according to claim 1, characterized in that: The mass ratio of chitosan to chloroacetic acid in step A2 is 1:(3.5-5).

3. The method for preparing a highly efficient adsorbent for uremia according to claim 1, characterized in that: The mass ratio of carboxymethyl chitosan to acylation agent in step A3 is 1:(7-10).

4. The method for preparing a highly efficient adsorbent for uremia according to claim 1, characterized in that: The mass ratio of carboxymethyl cellulose to sodium periodate in step B1 is 1:(0.9-1.1).

5. The method for preparing a highly efficient adsorbent for uremia according to claim 1, characterized in that: The mass ratio of the modified chitosan, 1,2-dichloroethane and the adsorbent material in step (1) is 1:(12-18):(4-7).

6. The method for preparing a highly efficient adsorbent for uremia according to claim 1, characterized in that: The mass ratio of the modified carboxymethyl cellulose to epichlorohydrin in step (2) is 1:(3.5-6).

7. A high-efficiency adsorbent obtained by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A cross-linked cellulose@molybdenum disulfide aerogel composite adsorbent, its preparation method and application

    CN113680328B

  • Adsorbing material as well as preparation method and application thereof

    CN115554975A